The halberd at Red Cliff Jian'an and the Three Kingdoms - Tian, Xiaofei 1971- (Cambridge, Massachusetts Published by the Harvard University Asia Center, 2018)
"The writings of the Jian'an era lay the foundation of China's classical poetry and literary criticism and its personages and events have inspired works of historical fiction and drama throughout Chinese history. This book investigates how these associations were closely related in their origins and subsequent metamorphoses"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Chinese poetry -- History and criticism. -- Qin and Han dynasties, 221 B.C.-220 A.D.; Chinese poetry -- History and criticism. -- Three kingdoms, 220-265.; Chinese literature -- History and criticism